Establishing Environmental Education on Students’ Environmental Literacy at Junior High School - Yanti Herlanti (Universitas Pendidikan Ganesha, 2022)
Currently, several cities show unhealthy conditions based on visual monitoring of the Air Quality Index. This problem certainly has an impact on declining public health. This study aims to measure the environmental literacy of schools participating in an environmental education project. This type of research is quantitative. The research method used in this research is a survey with a quantitative research design. Sampling was done by way of voluntary response sampling. The population is 24 public high schools with a total of 22,250 students. The research sample was 1,058 students from 19 schools. The method used in collecting data is a test. The instrument used in collecting data is a test question sheet. The techniques used to analyse the data are descriptive and inferential statistical analysis. The results showed that the average environmental literacy of students was in the moderate category. Aspects of awareness and attitude in environmental education show exemplary achievements. Other aspects, namely knowledge, skills, and participation, show sufficient achievement. The ability to identify and analyse environmental issues are in the less category. Even though the contribution of school activity factors in environmental projects to environmental literacy is very significant. The more actively the school participates in the project, the higher the students' environmental literacy.